Analisis Wacana Pesan Komunikasi Dakwah Ali Syari’ati - Dudi Rustandi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2017)
The purpose of this study is to explore the hidden message in the message of communication (da'wah) and the rhetoric conveyed by someone is a response from the social reality of the community that surrounds a Muballigh who shows his attitude and character. This gave birth to a distinctive character, different from other people's messages. It also refers to the social, political, economic, social and cultural context in which a person lives. This can be found from the preaching messages of Ali Shariati. Using the Teo A. Van Dijk model discourse analysis method, the researcher described the da'wah message based on the framework of the discourse elements; first, macro structure, Second; superstructure, third; micro structure. The use of the Discourse model is intended to interpret the latent intent of the message. The results of the study concluded that Ali Shari'ati's message of preaching emphasized a lot of aspects of aqeedah and morals, with the following characteristics; (1) The content of Shari'ati's message of preaching uses the historical sociological analysis methodology using reasoning or logic of comparison, (2) Tawhid becomes the basis of every content of Shari'ati's message, (3) The message is always progressive, this is characterized by new interpretations and meanings, (4) have a commitment to the culture and traditions of the local community, (5) Islam must be the basis of movement and side with the weak, (6) More emphasis on moral character.AbstrakTujuan penelitian ini adalah untuk mengeksplorasi pesan tersembunyi di dalam pesan komunikasi (dakwah) dan retorika yang disampaikan seseorang  merupakan respon dari realitas sosial masyarakat yang melingkupi seorang Muballigh yang menunjukan sikap dan karakternya. Hal tersebut melahirkan karakter pesan yang khas, berbeda dari pesan orang lain. Hal tersebut merujuk pula pada konteks sosial politik, ekonomi, sosial, dan budaya dimana seseorang hidup. Hal ini dapat ditemukan dari pesan-pesan dakwah Ali Syariati. Dengan menggunakan metode analisis wacana model Teo A. Van Dijk, peneliti menguraikan pesan dakwah berdasarkan kerangka elemen-elemen wacana; pertama, struktur makro, Kedua; superstruktur, ketiga ; struktur mikro. Penggunaan model Wacana dimaksudkan untuk menafsirkan maksud laten dari pesannya. Hasil penelitian dapat disimpulkan bahwa pesan dakwah Ali Syari’ati banyak menekankan aspek akidah dan akhlak, dengan ciri-ciri sebagai berikut; (1) Isi pesan dakwah Syari’ati menggunakan metodologi analisis sosiologi sejarah  dengan menggunakan penalaran atau logika komparasi, (2)Tauhid menjadi basis dalam setiap isi pesan dakwah Syari’ati, (3) Isi pesannya selalu menggungah dan progresif, hal ini dicirikan dengan penafsiran dan pemaknaan baru, (4) mempunyai komitmen terhadap budaya dan tradisi masyarakat setempat, (5) Islam harus menjadi basis pergerakan dan memihak kaum lemah, (6) Lebih menekankan aspek akidah akhlak.